Archaeology and anthropology - Garrow, Duncan; Yarrow, Thomas (Oxbow Books, 2010)
This book focuses on the relationship between the disciplines of archaeology and anthropology. Both disciplines arose from a common project: a desire to understand human social and cultural diversity. However, in recent years, archaeologys interest in anthropology has remained largely unreciprocated. To date, the causes and consequences of this imbalance have received little attention, particularly within anthropology. Including papers by eminent thinkers within both disciplines, this book sheds new light on issues of disciplinary identity. The contributors show how a lack of collaboration has.